Diagnostic and prognostic benefit of arterial spin labeling in subacute stroke - Thamm, Thoralf; Zweynert, Sarah; Piper, Sophie K.; Madai, Vince I.; Livne, Michelle; Martin, Steve Z.; Herzig, Cornelius X.; Mutke, Matthias Anthony; Siebert, Eberhard; Liebig, Thomas; Sobesky, Jan (Brain and behavior, 2019)
Abstract Background and Purpose: Brain perfusion measurement in the subacute phase of stroke may support therapeutic decisions. We evaluated whether arterial spin labeling (ASL), a noninvasive perfusion imaging technique based on magnetic resonance imaging (MRI), adds diagnostic and prognostic benefit to diffusion‐weighted imaging (DWI) in subacute stroke.